International antitrust enforcement and multi-market contact - Jay Pil Choi; Heiko A. Gerlach (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper analyzes international antitrust enforcement when multinational firms operate in several markets with antitrust authorities in each market. We are concerned with how the sustainability of collusion in one local market is affected by the existence of collusion in other markets when they are linked by demand relationships. The interdependence of collusion sustainability across markets leads to potential externalities in antitrust enforcement across jurisdictions. As a result, cartel prosecution can have a domino effect with the desistance of one cartel triggering the internal break-up of the cartel in the adjacent market. We further find that the equilibrium in antitrust authorities' enforcement decisions may exhibit non-linearity due to a free-rider problem as the global economy is more integrated. We also analyze the equilibrium antitrust enforcement and compare it with the globally optimal antitrust enforcement policy.
Keywords: D41; F1; L13; L41; 330; Collusion; antitrust enforcement; multi-market contact; Konzentrationspolitik; Wettbewerbspolitik; International; Nationalstaat; Multinationales Unternehmen; Gleichgewichtstheorie; Theorie